PENGEMBANGAN OBJEK WISATA AIR TERJUN AEK MARTUA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN ROKAN HULU - Ardi Saputra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Rokan Hulu Regency is an area that has a lot of tourism potential from Natural Resources, to arts and culture. Tourism is an overall activity related to tourism and is multidimensional and multidisciplinary in nature which emerges as a manifestation of the needs of each person and country as well as interactions between tourists and the local community, fellow tourists, local governments, and entrepreneurs. Tourism development is one form of tourism sector development that is very much needed in order to increase the attractiveness of tourists to visit. Well-managed tourism will also add to one of the Original Regional Income. The purpose of this study To find out the development of the Aek Martua Waterfall Tourism Object by the Rokan Hulu Regency Tourism and Culture Office, To find out the inhibiting factors for the development of Tourism Objects, plunge aek martua by the Department of Tourism and Culture of Rokan Hulu Regency. Based on the Regional Tourism Development Master Plan of Rokan Hulu Regency there are several factors found in the Aek Martua Waterfall area, namely: Activity, Aminity, Accessibility. And facilities. This study uses qualitative research methods, using purposive sampling techniques, this study uses data collection techniques of observation, interviews and documentation. To achieve the validity of the data in this study, researchers need to extend participation and triangulation.